Un centro di Ricerca per la Musica a Roma. Dall’IRCAM all’ampliamento dell’Auditorium “Parco Della Musica” (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
The text summarizes the preparatory conversation between Francesco Telli, Giorgio Nottoli and Anna Irene Del Monaco to set up the functional program of the degree thesis of Valentino Matteis and Andrew Iacobucci. The interview analyzes the most up-to-date needs of a research center for contemporary music to be implemented as an extension of the current functions of the Auditorium “Parco Della Musica” in Rome.